Antimicrobial Susceptibility of Shigella sonnei Isolates in Japan and Molecular Analysis of S. sonnei Isolates with Reduced Susceptibility to Fluoroquinolones - Hirose, Kenji (American Society for Microbiology, 2005)
We performed susceptibility testing with Shigella sonnei isolates from imported and domestic cases of infection in Japan during 2001 and 2002. Some S. sonnei isolates were resistant to nalidixic acid, tetracycline, and trimethoprim-sulfamethoxazole. Most of the nalidixic acid-resistant strains showed reduced susceptibility to fluoroquinolones but did not show fluoroquinolone resistance.